Teacher Educators Perspectives on The Use of Augmented Reality for Foreign Language - Perdana, Indra; Linggua Sanjaya Usop; Mas'ud Muhammadiah; Pandu Adi Cakranegara; Lazarus Linarto; Arifin, Ardian (JTP - Jurnal Teknologi Pendidikan, 2021)
The purpose of this research is to share reflections on Augmented Reality (AR) technology as an upgrade tool for foreign language development. Exploring the short but considerable literature research, this post discusses AR technology for the rise in the philosophy of upgrading, upgrading teacher nursery in position, teachers, pupils, customs, infrastructure, and sustainability, using the framework of activities outlines the suitability of the use of upgrading technology in development programs. For analysis, AR technology has essential benefits for language development; however, it is not suitable for all language types. Not only that, but this information also offers solid recommendations for activities that are enhanced with AR in 4 skills as well as language-specific applications. This information has some relevance for instructors, teachers, researchers, and creators of Augmented reality content.